Intracoronary Delivery of Self-Assembling Heart-Derived Microtissues (Cardiospheres) for Prevention of Adverse Remodeling in a Pig Model of Convalescent Myocardial Infarction. (May 2015) - Gallet, Romain; Tseliou, Eleni; Dawkins, James; Middleton, Ryan; Valle, Jackelyn; Angert, David; Reich, Heidi; Luthringer, Daniel; Kreke, Michelle; Smith, Rachel; Marbán, Linda; Marbán, Eduardo
<x xml:space="preserve">Abstract</x> Background— Preclinical studies in rodents and pigs indicate that the self-assembling microtissues known as cardiospheres may be more effective than dispersed cardiosphere-derived cells. However, the more desirable intracoronary route has been assumed to be unsafe for cardiosphere delivery: Cardiospheres are large (30–150 μm), raising concerns about likely microembolization. We questioned these negative assumptions by evaluating the safety and efficacy of optimized intracoronary delivery of cardiospheres in a porcine model of convalescent myocardial infarction. Methods and Results— First, we standardized the size of cardiospheres by modifying culture conditions. Then, dosage was determined by infusing escalating doses of cardiospheres in the left anterior descending artery of naive pigs, looking for acute adverse effects. Finally, in a randomized efficacy study, 14 minipigs received allogeneic cardiospheres (1.3×106) or vehicle 1 month after myocardial infarction. Animals underwent magnetic resonance imaging before infusion and 1 month later to assess left ventricular ejection fraction, scar mass, and viable mass. In the dosing study, we did not observe any evidence of microembolization after cardiosphere infusion. In the post-myocardial infarction study, cardiospheres preserved LV function, reduced scar mass and increased viable mass, whereas placebo did not. Moreover, cardiosphere decreased collagen content, and increased vessel densities and myocardial perfusion. Importantly, intracoronary cardiospheres decreased left ventricular end-diastolic pressure and increased cardiac output. Conclusions— Intracoronary delivery of cardiospheres is safe. Intracoronary cardiospheres are also remarkably effective in decreasing scar, halting adverse remodeling, increasing myocardial perfusion, and improving hemodynamic status after myocardial infarction in pigs. Thus, cardiospheres may be viable therapeutic candidates for intracoronary infusion in selected myocardial disorders.